Behavior of AV synchrony pacing mode in a leadless pacemaker during variable AV conduction and arrhythmias. (20th May 2021) - Garweg, Christophe; Khelae, Surinder Kaur; Chan, Joseph Yat Sun; Chinitz, Larry; Ritter, Philippe; Johansen, Jens Brock; Sagi, Venkata; Epstein, Laurence M.; Piccini, Jonathan P.; Pascual, Mario; Mont, Lluis; Willems, Rik; et al.
Abstract: Introduction: MARVEL 2 assessed the efficacy of mechanical atrial sensing by a ventricular leadless pacemaker, enabling a VDD pacing mode. The behavior of the enhanced MARVEL 2 algorithm during variable atrio‐ventricular conduction (AVC) and/or arrhythmias has not been characterized and is the focus of this study. Methods: Of the 75 patients enrolled in the MARVEL 2 study, 73 had a rhythm assessment and were included in the analysis. The enhanced MARVEL 2 algorithm included a mode‐switching algorithm that automatically switches between VDD and ventricular only antibradycardia pacing (VVI)‐40 depending upon AVC status. Results: Forty‐two patients (58%) had persistent third degree AV block (AVB), 18 (25%) had 1:1 AVC, 5 (7%) had variable AVC status, and 8 (11%) had atrial arrhythmias. Among the 42 patients with persistent third degree AVB, the median ventricular pacing (VP) percentage was 99.9% compared to 0.2% among those with 1:1 AVC. As AVC status changed, the algorithm switched to VDD when the ventricular rate dropped less than 40 bpm. During atrial fibrillation (AF) with ventricular response greater than 40 bpm, VVI‐40 mode was maintained. No pauses longer than 1500 ms were observed. Frequent ventricular premature beats reduced the percentage of AV synchrony. During AF, the atrial signal was of low amplitude and there was infrequent sensing. Conclusion: The mode switching algorithm reduced VP in patients with 1:1 AVC and appropriately switched to VDD during AV block. No pacing safety issues were observed during arrhythmias.